Funkcjonalność serwisu WWW a wybór systemu CMS - Szkodzin, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Efficient management of a website - a company's or a private one - is connected with a necessity to implement the CMS (Content Management System). Many applications of this type are available on the market, either paid or offered under the GNU GPL license. The purpose of this article is to present the most important criteria to be considered while choosing the content management system, so that it helps to accomplish in the highest degree the functional guidelines of the given website. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 399-406